2019
DOI: 10.1021/acs.iecr.9b05181
|View full text |Cite
|
Sign up to set email alerts
|

Process Operability Algorithms: Past, Present, and Future Developments

Abstract: In this Article, the recently developed multimodel and NLP-based operability approaches are reviewed and further developed in terms of theory, application, and software infrastructure. Classical process operability concepts are also revisited and contrasted with new extensions present in both approaches. A focus is given on the comparison between distinct measures of the operability index and the handling of infeasible portions of the desired operating region. For the software infrastructure outcome, a framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Operability describes in general the inherent ability of the plant to perform satisfactorily under conditions different from the nominal design conditions, which can include the requirement to adjust to changes in operating conditions, disturbances, product specification, and so on 50,51 . Extensive efforts have been made in the PSE community over the past several decades to quantify process operability performance from different aspects as summarized below (see detailed reviews 11,40,50,82 ): Steady‐state and dynamic flexibility analysis — to determine the maximum uncertainty/disturbance that can be handled at the nominal operating point in a fixed design configuration 83‐85 Steady‐state and dynamic controllability analysis — to determine the “best” dynamic performance achievable for a system under closed‐loop control 48,51,86 Operability‐based analysis — to determine whether a controller can perform its mission under the constraints posed by the existing input variables and desirable output variables using linear/nonlinear input/output mapping methods 31,87 …”
Section: Research Opportunities and Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Operability describes in general the inherent ability of the plant to perform satisfactorily under conditions different from the nominal design conditions, which can include the requirement to adjust to changes in operating conditions, disturbances, product specification, and so on 50,51 . Extensive efforts have been made in the PSE community over the past several decades to quantify process operability performance from different aspects as summarized below (see detailed reviews 11,40,50,82 ): Steady‐state and dynamic flexibility analysis — to determine the maximum uncertainty/disturbance that can be handled at the nominal operating point in a fixed design configuration 83‐85 Steady‐state and dynamic controllability analysis — to determine the “best” dynamic performance achievable for a system under closed‐loop control 48,51,86 Operability‐based analysis — to determine whether a controller can perform its mission under the constraints posed by the existing input variables and desirable output variables using linear/nonlinear input/output mapping methods 31,87 …”
Section: Research Opportunities and Perspectivesmentioning
confidence: 99%
“…Stepping to the equipment‐based steady state and dynamic design, significant progresses have been made in the PSE community to explore design under uncertainty under multiple time scales. Detailed reviews can be found in Yuan et al 97 and Burnak et al, 82 while an indicative list is given as follows: Steady‐state flexibility with multiperiod design — for example, heat exchanger network, 83 mass and heat exchange network 98 Dynamic flexibility with multiperiod design — for example, distillation column, 99 air separation system 100 Design with controllability considerations — for example, reaction‐separation system, 101 divided wall column 102 Operability‐based design — for example, membrane reactor 31,103 Integrated design and control — for example, combined heat and power system, 104 reactive distillation 92,105 …”
Section: Research Opportunities and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Past operability studies have also considered the application of operability to control strategies [4,5], process intensification [6,7], and design optimization [8,9]. The operability framework has been extensively studied from a steady-state point of view [10], in which the graphical regions used consisted of mainly stable points of operation [11,12].…”
Section: Introductionmentioning
confidence: 99%